PJMHS 2021
DOI: 10.53350/pjmhs2115113112
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics in Neonates with Hyperbilirubinemia Receiving Phototherapy

Abstract: Study Objectives: To compare the mean duration of phototherapy in neonates with hyperbilirubinemia receiving phototherapy with vs. without probiotics. Study Design and Settings: It was a randomized controlled trial carried at Department of Pediatrics, DHQ Hospital Kasur from Jan 2021 to June 2021. Patients and Methods: The present research involved 94 neonates of both genders aged between 2 to 28 days of life diagnosed of neonatal hyperbilirubinemia (serum bilirubin level ≥15mg/dL and direct bilirubin level ≤1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…If you don't like these things, then people who like them will adopt them and you will tolerate this action. 6 It can also be terminologically defined as that it is the name of such an attribute that is opposite to prejudice, individualism, coercion, obstinacy and in which an action is permitted and permissible with exceptions. In which the concepts and ideas of people of other religions should be tolerated with patience.…”
Section: Definition Of Tolerancementioning
confidence: 99%
“…If you don't like these things, then people who like them will adopt them and you will tolerate this action. 6 It can also be terminologically defined as that it is the name of such an attribute that is opposite to prejudice, individualism, coercion, obstinacy and in which an action is permitted and permissible with exceptions. In which the concepts and ideas of people of other religions should be tolerated with patience.…”
Section: Definition Of Tolerancementioning
confidence: 99%
“…On the other hand, Nouri et al prescribed PediLact as a synbiotic in icteric term and preterm neonates > 35 weeks of GA and revealed significant differences in the rate of bilirubin reduction and duration of hospital stay in the intervention group (3). In numerous studies, the findings showed that the addition of oral probiotics/prebiotics/synbiotics to phototherapy is associated with a higher bilirubin reduction rate, reduced phototherapy duration, and shorter hospitalization (31)(32)(33)(34)(35). In addition, S. boulardii, in combination with phototherapy, was effective and safe in reducing bilirubin levels and duration of phototherapy in icteric premature infants in Hu et al's study (36).…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%